Alat Bantu Pembuatan dan Monitoring Susu untuk Anak Kambing: Indonesia - Vauzie, Hanif Muhammad; Rashal, Alif Hidayah; Yuwono, Tito; Imawati, Iftitah; Adianto, Nur (UII, 2026)
On dairy goat farms, kids are fed formula milk. This is because formula milk is cheaper than their mother's milk. Formula milk to be fed to kids must be heated to a temperature of around 35°C-37°C. Therefore, equipment capable of heating milk stably within this temperature range is required. Furthermore, dairy goat farm owners are concerned with monitoring their workers to ensure that they are feeding the kids milk correctly and in a disciplined manner. In this study, a prototype milk-making aid was designed and built that can produce temperatures within this range 35°C –37 °C and can be monitored remotely. Performance test results showed that the device can heat milk to 37°C in an average of 30 minutes with a maximum deviation of ±0.5°C, stir evenly for 5 minutes, and maintain the temperature and volume within the target range.